2019
DOI: 10.1007/978-981-13-7564-4_19
|View full text |Cite
|
Sign up to set email alerts
|

An Identity-Based Encryption Scheme for Data Security in Fog Computing

Abstract: This book series publishes research on the analysis and development of algorithms for intelligent systems with their applications to various real world problems. It covers research related to autonomous agents, multi-agent systems, behavioral modeling, reinforcement learning, game theory, mechanism design, machine learning, meta-heuristic search, optimization, planning and scheduling, artificial neural networks, evolutionary computation, swarm intelligence and other algorithms for intelligent systems. The book… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…It can be used to perform heavy computation operations and reduce the computational overhead required on resource-constrained devices. Nonetheless, few works have focused on security and privacy in fog computing [23].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be used to perform heavy computation operations and reduce the computational overhead required on resource-constrained devices. Nonetheless, few works have focused on security and privacy in fog computing [23].…”
Section: Related Workmentioning
confidence: 99%
“…Literature [25]- [27] has applied ciphertext-policy attribute-base encryption (CP-ABE) to establish secure access control over encrypted data in fog computing, thereby enabling a data owner to specify the access policy over a universe of attributes that a user needs to decrypt the ciphertext. A further proposed scheme in [23] uses identity-based cryptography to provide secure communication through unauthorized users in fog. The authors in [43] presented an ID-based PRE scheme with auxiliary input.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramadan et al 16 investigated identity‐based encryption scheme under the RSA assumption and providing equality test. Meshram et al 17,18 presented efficient transformation model for cryptosystem and short signature schemes using chaotic maps under cloud computing environment with fuzzy user data sharing Farjana et al 19 demonstrated the new identity‐based encryption technique that confirms protected information transmission to certified users and showed its implementation in fog computing.…”
Section: Introductionmentioning
confidence: 99%
“…The author also proposed the fog computing base face identification and resolution framework used to improve the processing capacity to save the bandwidth and observes the protection and privacy issues. A privacy security scheme is for the data encryption and integrity finder to resolve the confidentiality, availability issue, and integrity in the data processing (Farjana, et al 2020).…”
Section: Introductionmentioning
confidence: 99%